Influence of Organizational Culture on Employee Performance at Yayasan Pendidikan Al Hikmah - Moh. Maulana Waqid Kurniawan (INCOME: Innovation of Economics and Management, 2022)
This study aims to explore the impact of organizational culture on employee performance at Yayasan Pendidikan Al Hikmah, an institution that operates with a full-day school system based on international standards. Using Cameron and Quinn’s (2006) framework, the research employs a quantitative approach, utilizing surveys to gather data from employees. The findings reveal that the organization’s culture has a significant impact on employee performance, with an average organizational culture score of 4444 and an employee performance score of 43670, both categorized as "Very Good." Furthermore, the study concludes that organizational culture contributes 26.3% to employee performance at the foundation, highlighting the importance of fostering a strong organizational culture for enhanced employee outcomes.